Measuring L2 Essay Rating Strategy: Scale Development and Preliminary Validation - Xu, Ying (Frontiers in Education, 2018)
Given the lack of an L2 essay rating strategy scale, this study aims to develop and evaluate an instrument measuring College English Test Band 4 (CET4) essay raters' rating strategy. 14 raters were first invited to mark 10 mock essays while conducting think-aloud in order to generate a pool of scale items. After piloted on three raters, the initial version of the questionnaire including 28 items was established, among which 22 items were related with cognitive strategies (CS) and the rest meta-cognitive strategies (MCS). Then it was administered to a sample of 450 raters in four marking centers around China. Item-total correlation, exploratory factor analysis (EFA), and reliability analysis were conducted to evaluate its psychometric properties. It was found that the final version contained 12 items, and the four-factor solution (Self-evaluate, Decide, Diagnose, and Compare) could explain 59.92% of the total variance. Cronbach's Alpha reached 0.73 for the whole questionnaire. The results suggest that the instrument has acceptable reliability and adequate validity.